Famous Fails : Mighty Mistakes, Mega Mishaps & How a Mess can Lead to Success! - Boyer, Crispin (Washigton National Geographic, 2016)
This fun book of quirky failures and famous flops will keep kids laughing while they learn the importance of messing up in order to get it right.
Include Color Illustrations
Keywords: Success -- Errors -- Failure (Psychology)